OVERSIZED COALITION GOVERNMENTS OF CENTRAL EUROPEAN COUNTRIES: FACTORS OF FORMATION AND ESTIMATION OF GOVERNMENT STABILITY - Лопата, М.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
This study is comparative exploration of minimum-winning coalition governments in Central European countries. In article is introduced the short history of formation and termination surplus coalition governments, construction and termination of governments. The index of government stability for surplus governments is evaluated in distinct countries.